Challenge-based and Competency-based Assessments in an Undergraduate Programming Course - Sidhu, Gaganpreet; Srinivasan, Seshasai; Muhammad, Nasim (International Journal of Emerging Technologies in Learning (iJET), 2021)
In this work, we investigate an optimal assessment strategy to measure student learning in the first-year undergraduate engineering course at X-Department at X University. Specifically, we evaluate and compare challenge-based and competency-based assessment strategies. In the challenge-based approach, the students are required to design a C++-based application that meet the required design objectives. The competency-based assessment involves assessing learning by asking a variety of pointed questions pertaining to a single or a small group of concepts. After studying the performance of 207 students, we found that in the challenge-based assessment, due to the complex nature of the questions that assess numerous concepts simultaneously, students who are not very thorough with even one or two concepts fared very poorly since they were unable to finish the challenge and present a functional prototype of the program. On the other hand, the competency-based assessment allowed for a more balanced approach in which the students’ learning was reflected more accurately by their performance in the various assessments.